Effect of salinity in the first phase of salt stress on leaf cell-wall components of maize with special reference to cell-wall extensibility - Uddin, Md. Nesar; Justus Liebig University Giessen (My University, 2012)
Summary of Experiment 2A method of cell-wall isolation was optimized, and cell walls were separated into two fractions (250-405 µm fraction and > 405 µm fraction). Both the cell-wall fractions showed negative color test with iodine reagent and thus were free from starch content. Cellulose, neutral sugars and uronic acid responses due to the salt treatment were obvious from the 250-405 µm cell-wall fraction. On the other hand, the > 405 µm cell-wall fraction did not show much variation in results due to the salt treatment. The 250-405 µm fraction was dominated by cell wall from mesophyll and epidermal tissues, while the > 405 µm fraction was dominated by cell wall from vascular and fiber tissues. It was evident from the analyses that the 250-405 µm cell-wall fraction gave the results of interest under salt stress. Thus results showed clearly that the 250-405 µm cell-wall fraction may be the most important fraction for studying salt-induced changes in cell-wall compositions. Summary of Experiment 2Growth inhibition of crops in the first phase of salt stress is one of the core questions in the field of stress physiology and the mechanisms are not yet precisely known. Maize is able to maintain shoot turgor pressure during the first phase of salt stress. Assimilate supply to the growing tissue under salt stress is not found limiting under salt stress. Additionally, water uptake by maize plants from the saline solution did not limit growth. It has been reported that the maintenance of apoplastic acidification under saline condition contributes to the better performance of the salt-resistant genotype SR 03. Surprisingly, another salt-resistant genotype SR 12 cannot maintain apoplastic acidification during the first phase of salt stress despite of its better growth compared to Pioneer 3906. Thus apoplastic acidification only partly explains the strong growth reduction during the first phase of salt stress. So additional factors must be involved in reducing the cell-wall extensibility. It is presumed that the chemical composition of the cell wall may be changed during the first phase of salt stress, which may play a crucial role to reduce cell-wall extensibility in a differential manner in salt-sensitive (e.g. Pioneer 3906) and salt-resistant (e.g. SR 12) genotypes.The present study was conducted to examine the hypotheses that (i) cell-wall polysaccharides, which result in tightening of cell wall to reduce plant growth, are changed in the growing leaves during the first phase of salt stress; (ii) leaf-growth reduction is accompanied with changes in leaf cell-wall monomeric phenols and various diferulates during the first phase of salt stress; (iii) salt stress-induced changes in cell-wall components are different in the salt-sensitive Pioneer 3906 and the salt-resistant SR 12. Following conclusions are supported from this study:(i) Salt treatment caused a strong inhibition of shoot growth with a concomitant increase in the ratio of cell-wall dry mass and shoot fresh mass, and a decrease in cell-wall cellulose concentrations in both Pioneer 3906 and SR 12. NaCl caused a large increase in the concentrations of total and non-methylated uronic acid in both salt-sensitive Pioneer 3906 and salt-resistant SR 12. It is concluded that a low accumulation of non-methylated uronic acid in leaf cell-wall may, among other mechanisms, contribute to salt resistance in the first phase of salt stress. (ii) Salt stress favors cell-wall components participating in oxidative cross-linking in elongating shoot tissue of salt-sensitive maize genotype Pioneer 3906. The salt-sensitive genotype Pioneer 3906 had higher concentrations of ferulic acid (FA) and various diferulic acids (DFAs) during salt stress, while in the new hybrid SR 12 these parameters were unchanged. Both genotypes showed an increase in arabinose, which is the molecule at which FA and DFA are coupled to interlocking glucuronoarabinoxylan (GAX) fibers. Results are consistent with the concept that accelerated oxidative fixation of shape contributes to growth suppression in the salt-sensitive genotype during the first phase of salt stress.(iii) The onset of the accumulation of non-methylated uronic acid was delayed in SR 12, which indicates that this may be one reason for the better growth performance of this genotype under salt stress compared to Pioneer 3906. Also, salt-sensitive genotype Pioneer 3906 showed a significantly higher increase in ferulic acid, total diferulic acid and total monomeric phenols in the youngest shoot during the first phase of salt stress compared to SR 12.

- Zusammenfassung von Experiment 1Das Verfahren zur Zellwandisolierung wurde optimiert und die Zellwände wurden in zwei Fraktionen (250-405 µm Fraktion und > 405 µm Fraktion) getrennt. Beide Zellwandfraktionen zeigten ein negatives Ergebnis im Iodtest und
Keywords: ddc:630